Core body temperature responses during competitive sporting events: a narrative review - Singh, Gurpreet; Bennett, Kyle; Taylor, Lee; Stevens, Christopher (Biology of Sport, 2023)
Due to the lack of research in real-world sports competitions, the International Olympic Committee, in 2012, called for data characterising athletes’ sport and event-specific thermal profiles. Studies clearly demonstrate that elite athletes often attain a core body temperature (Tc) ≥ 40°C without heat-related medical issues during competition. However, practitioners, researchers and ethical review boards continue to cite a Tc ≥ 40°C (and lower) as a threshold where athlete health is impacted (an assumption from laboratory studies). Therefore, this narrative review aims to: (i) summarise and review published data on Tc responses during competitive sport and identify key considerations for practitioners; (ii) establish the incidence of athletes experiencing a Tc ≥ 40°C in competitive sport alongside the incidence of heat illness/heat stroke (EHI/EHS) symptoms; and (iii) discuss the evolution of Tc measurement during competition. The Tc response is primarily based on the physical demands of the sport, environmental conditions, competitive level, and athlete disability. In the reviewed research, 11.9% of athletes presented a Tc ≥ 40°C, with only 2.8% of these experiencing EHI/EHS symptoms, whilst a high Tc ≥ 40°C (n = 172; Tc range 40–41.5°C) occurred across a range of sports and environmental conditions (including some temperate environments). Endurance athletes experienced a Tc ≥ 40°C more than intermittent athletes, but EHI/EHS was similar. This review demonstrates that a Tc ≥ 40°C is not a consistently meaningful risk factor of EHI/EHS symptomology in this sample; therefore, Tc monitoring alongside secondary measures (i.e. general cognitive disturbance and gait disruption) should be incorporated to reduce heat-related injuries during competition.